The need for skills development among SMTEs in Mnquma Municipality, South Africa - Siyabonga Mxunyelwa (Interdisciplinary Journal of Rural and Community Studies)
This study aims to examine the impact of educational qualifications and skills development on the managerial competencies and performance of Small and Medium Tourism Enterprises (SMTEs) in Mnquma Municipality, Eastern Cape, South Africa. The research design employed in this study is descriptive, and a total of 64 SMTE owners and managers were selected through purposive sampling. The data collection process involved the use of self-administered questionnaires, which included items on demographic information and insights into training and skills development initiatives. The findings of the study indicate that 51.7% of the respondents hold a diploma or degree, while only 8.6% possess postgraduate qualifications, suggesting the existence of a potential gap in advanced managerial skills. A significant majority of the respondents (77.6%) agree that training workshops, seminars, and conferences are beneficial for enhancing managerial competencies. However, the study also reveals that there are barriers preventing access to these opportunities, as indicated by 22.4% of respondents who were undecided or disagreed on their value. Overall, the study emphasises the importance of tailored training programs that address the specific needs of SMTE managers in rural areas. Enhanced skills development is crucial for enhancing the operational efficiency and sustainability of SMTEs, thereby contributing to broader economic growth. In conclusion, investing in skills development initiatives can significantly enhance the performance and sustainability of SMTEs in Mnquma Municipality, thus fostering economic growth and development in the region. This study provides valuable insights for policymakers and stakeholders seeking to support the small business sector in rural areas.